Relacje rodzinne w obliczu kary pozbawienia wolności - Nymś-Górna, Agnieszka (Człowiek i Społeczeństwo, 2025)
This article addresses the issue of how families of incarcerated individuals function, highlighting the multidimensional nature of the crisis that affects the relatives of those serving prison sentences. Each dimension entails distinct emotional, social, and practical challenges, both for the inmate and for their loved ones. Particular attention is given to the disorganization of family life, stigmatization, loneliness, parenting difficulties, and the weakening of emotional bonds as a result of penal isolation. The article emphasizes the importance of preparing families for reintegration, the challenges they face, and the need for systemic support that includes not only the incarcerated individuals but also their families. It also proposes potential support measures aimed at mitigating the negative consequences of imprisonment and increasing the chances of successful social reintegration.